Fintech Adoption and Commercial Banks’ Environmental Performance: Do Green Accounting Practices Matter? - Ywana Maher Lamey Badrous; Omar Ikbal Tawfik; Hamada Elsaid Elmaasrawy; Mohamed Ibrahim Srour; Mohammed Ahmed Ahmed Sharaf (International Journal of Financial Studies, 2025)
From reviewing the literature, there was still a scarcity of research about direct and indirect relationships between fintech adoption (FA) and banks’ environmental performance (BEP), particularly in developing countries. Therefore, this is a pioneering study that empirically explored the impacts of FA on BEP in the Middle East (ME) region, considering the mediating role of green accounting practices (GAPs)—such as green banking practices (GBPs), green finance (GF), and circular economy practices (CEPs)—based on legitimacy and ecological modernization (EM) theories to address these research gaps. Based on a structured survey and convenience sampling technique, the primary data were obtained from a sample of 500 members of staff from banks in Saudi Arabia, Bahrain, Egypt, Oman, Iraq, and Jordan. The structural equation model (SEM) was utilized to investigate the relationships among this study’s variables. The findings indicated that FA positively and significantly impacts GBPs, GF, CEPs, and BEP, which answered the first research question. Furthermore, the linkage between FA and BEP is positively and significantly mediated by GBPs, GF, and CEPs; thus, the second research question was answered. The findings provide bank executives and policy makers with valuable understanding and suggestions to deploy more investments in eco-friendly practices to enhance the environmental performance (EP), societal legitimacy, and achieve competitive advantage. Additionally, collaboration among the banking institutions, governments, and international firms is essential to promote FA and GAPs and enhance the EP.